2017
DOI: 10.1155/2017/8686207
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Garlic-Derived S-Allylmercaptocysteine on IL-1β-Stimulated Chondrocytes by Regulation of MMPs/TIMP-1 Ratio and Type II Collagen Expression via Suppression of NF-κB Pathway

Abstract: Background Garlic-derived S-allylmercaptocysteine (SAMC) has widely been used in many disease therapies. However, the potential effects and mechanism of SAMC on IL-1β-stimulated chondrocytes are unclear. Methods Chondrocytes were isolated, and 5 ng/mL of IL-1β was added to mimic the in vitro osteoarthritis (OA) model. SAMC (20 and 60 μM) was used for the treatment in OA model. Cell viability was assessed by MTT method. Western blotting, Quantitative RT-PCR, and ELISA were performed to evaluate the mechanisms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
1
8
1
1
Order By: Relevance
“…Studies have shown that IL-1β plays an important role in the progression of OA by promoting the degeneration and apoptosis of chondrocytes, and it has been widely used to establish OA cell models 15, 16. This is consistent with our results showing that IL-1β stimulated miR-10a-5p expression in both human and murine primary chondrocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that IL-1β plays an important role in the progression of OA by promoting the degeneration and apoptosis of chondrocytes, and it has been widely used to establish OA cell models 15, 16. This is consistent with our results showing that IL-1β stimulated miR-10a-5p expression in both human and murine primary chondrocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Immunohistochemistry examination was carried out as previously described. 6 Briefly, sections were deparaffinized, rehydrated, and blocked with 10% normal goat serum. Then the primary antibody (anti-rat Col II antibody, anti-p65 antibody, Abcam) were incubated overnight, following biotin-labeled secondary antibodies for 1 hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Chondrocytes isolation was conducted as previously described with modification. 6 Primary rat chondrocytes were seeded in 6-well plates. Nrf2 loss-of-function approaches were achieved by infecting the cells with adenovirus of miNrf2 (Ad-miNrf2) and miScramble (Ad-Scramble) 11 in serum free DMEM for 8 hours and then changed to DMEM supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…TNF-α and IL-1β can promote chondrocytes to release more inflammatory factors, such as nitric oxide (NO), MMPs and ADAMTS. IL-1β can also promote the secretion of TNF-α, which itself exerts effects on IL-1β, promotes the synthesis of MMPs, inhibits the synthesis of proteoglycans and causes cartilage loss [ 61 , 62 ].…”
Section: Cartilage Homeostasismentioning
confidence: 99%